Probing Redox Responses and DNA Interactions in Drug Discovery - Hüseyin Oğuzhan Kaya; Ceylin Bozdemir; Hüseyin İstanbullu; Seda Nur Topkaya (Drugs and Drug Candidates, 2025)
Background/Objectives: The thiazolo [5,4-d]pyrimidine scaffold is a class of drugs known for its anticancer, antitumor, anti-inflammatory, and antimicrobial properties. In this study, the electrochemical properties of novel thiazolo [5,4-d]pyrimidine derivatives and their interactions with DNA were characterized for the first time using voltammetric methods. Determining the interactions of new drug candidate molecules with DNA is crucial for drug development studies and is the main objective of this research. Methods: Both molecules were immobilized on the surface of the electrodes by passive adsorption, and their electrochemical properties were determined by voltammetric methods through reduction currents. Their interactions with DNA were carried out in the solution phase and examined by the changes in the oxidation peak potential and current of the guanine base. Results: For both molecules, it was determined that the electrochemical reduction processes are diffusion-controlled and irreversible, with an equal number of protons and electrons being transferred during this process. The detection limits for TP-NB (4-chloro-N-(5-chlorothiazolo [5,4-d]pyrimidin-2-yl)-3-nitrobenzamide) and TP-PC (1-(2-(4-(4-carbamoylpiperidin-1-yl)-3-nitrobenzamido)thiazolo [5,4-d]pyrimidin-5-yl)piperidine-4-carboxamide) were determined to be 12 µg/mL and 16 µg/mL, respectively. As a result of the interaction between both molecules with DNA, the guanine oxidation current decreased. It was found that TP-NB could act as an intercalator, while TP-PC could affect DNA electrostatically, both showing toxic effects on DNA. Conclusions: An electrochemical method was developed for the rapid, cost-effective, and sensitive detection of both molecules and their DNA interactions. Both compounds exhibited notable affinity towards DNA, as evidenced by significant changes in oxidation peak currents, shifts in peak potentials, and calculated toxicity values. These findings suggest their potential use as DNA-interacting drugs, such as anticancer and antimicrobial agents. Our study offers a quick, cost-effective, and reliable electrochemical approach for the evaluation of drug–DNA interactions.